2018
DOI: 10.1002/clc.22994
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular base/apex ratio in the assessment of pediatric pulmonary arterial hypertension: Results from the European Pediatric Pulmonary Vascular Disease Network

Abstract: The RVES b/a ratio decreased in children with PAH compared with age- and sex-matched healthy subjects. The RVES b/a ratio inversely correlated with both echocardiographic and hemodynamic indicators of increased RV pressure afterload and with NYHA class, suggesting that RVES b/a ratio reflects disease severity in PAH children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…In agreement with our recent findings and recommendations, [2][3][4] Dandel and Hetzer suggest to use the RVES b/a ratio in combination with more established measures of RV function, and the authors explain the advantages of a multi-parameter analysis to assess myocardial changes under pathological conditions (as evident in PAH), where parallel measurements of the load-dependency of RV size, geometry, and pump function prove useful for a detailed RV evaluation. 1 Other integrative approaches using different combinations of parameters also included data on RV afterload.…”
Section: To the Editorsupporting
confidence: 85%
See 2 more Smart Citations
“…In agreement with our recent findings and recommendations, [2][3][4] Dandel and Hetzer suggest to use the RVES b/a ratio in combination with more established measures of RV function, and the authors explain the advantages of a multi-parameter analysis to assess myocardial changes under pathological conditions (as evident in PAH), where parallel measurements of the load-dependency of RV size, geometry, and pump function prove useful for a detailed RV evaluation. 1 Other integrative approaches using different combinations of parameters also included data on RV afterload.…”
Section: To the Editorsupporting
confidence: 85%
“…2 As suggested by Dandel and Hetzer we herein assessed the correlation between RVES b/a ratio and the indexed PVR (PVRi), which was found to be significant (ρ = −0.571, P < 0.001). Furthermore, S 0 showed a significant negative correlation with mPAP (ρ = −0.428, P = 0.009) and PVRi (ρ = −0.451, P = 0.003), TAPSE had a negative correlation only with PVRi (ρ = −0.439, P = 0.004), while TAPSE and mPAP only showed a trend toward a negative correlation (ρ = −0.291, P = 0.085), suggesting that single systolic RV function parameters such as the TAPSE or S`cannot provide a detailed information on RV function and hemodynamics of the patient.In agreement with our recent findings and recommendations, [2][3][4] Dandel and Hetzer suggest to use the RVES b/a ratio in combination with more established measures of RV function, and the authors explain the advantages of a multi-parameter analysis to assess myocardial changes under pathological conditions (as evident in PAH), where parallel measurements of the load-dependency of RV size, geometry, and pump function prove useful for a detailed RV evaluation. 1 Other integrative approaches using different combinations of parameters also included data on RV afterload.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…1 In that study, the RVES b/a ratio revealed a high ability to distinguish children with PAH from healthy children and might therefore be useful for initial detection of children with previously unknown PAH. As expected, the RVES b/a ratio inversely correlated with both echocardiographic and hemodynamic indicators of increased overload.…”
Section: Diagnostic and Prognostic Value Of Echocardiography In Pulmomentioning
confidence: 77%
“…We read with great interest the study by Koestenberger et al, which was recently published in Clinical Cardiology, aiming to assess the usefulness of the right ventricle end-systolic basal-apical diameter ratio (RVES b/a) for initial diagnosis and follow-up of pediatric patients with pulmonary arterial hypertension (PAH). 1 In that study, the RVES b/a ratio revealed a high ability to distinguish children with PAH from healthy children and might therefore be useful for initial detection of children with previously unknown PAH. As expected, the RVES b/a ratio inversely correlated with both echocardiographic and hemodynamic indicators of increased overload.…”
Section: Diagnostic and Prognostic Value Of Echocardiography In Pulmomentioning
confidence: 77%